2016
DOI: 10.1038/ncomms12552
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid bio-photo-electro-chemical cells for solar water splitting

Abstract: Photoelectrochemical water splitting uses solar power to decompose water to hydrogen and oxygen. Here we show how the photocatalytic activity of thylakoid membranes leads to overall water splitting in a bio-photo-electro-chemical (BPEC) cell via a simple process. Thylakoids extracted from spinach are introduced into a BPEC cell containing buffer solution with ferricyanide. Upon solar-simulated illumination, water oxidation takes place and electrons are shuttled by the ferri/ferrocyanide redox couple from the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 42 publications
3
80
0
3
Order By: Relevance
“…Bioelectricity from thylakoid membrane isolated from the cell apparatus has been achieved in response to light. [4][5][6] However, whole microbes have the advantage of being a self-sustained and self-repairing, which greatly impacts the durability of the bioelectrochemical cell.…”
Section: Introductionmentioning
confidence: 99%
“…Bioelectricity from thylakoid membrane isolated from the cell apparatus has been achieved in response to light. [4][5][6] However, whole microbes have the advantage of being a self-sustained and self-repairing, which greatly impacts the durability of the bioelectrochemical cell.…”
Section: Introductionmentioning
confidence: 99%
“…[24] Our approach to enhance current and power generation by IR radiation is independent of such optimizations. The results reported in this work could provide a viable route to increase the efficiency and power output of BPVCs relying on mobile RMs as converters of energy.…”
Section: Sixfold Increase In Power Of Bpvcs Upon Ir Irradiationmentioning
confidence: 99%
“…[22] Put in perspective, 47 PW is approximately 1700 times the projected global energy consumption in 2050. [24] However, the bandgap of Si (E g = 1.1 eV) renders this technology insensitive to radiation for λ > 1100 nm, thus excluding potential harvesting of 21% of the AM1.5 solar radiation. In a recent work performed by Pinhassi et al, a beneficial tandem combination of a SiSC and a TM-based BPVC was demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…In natural photosynthesis, NADPH (reducing equivalent) and ATP (chemical energy) are produced via electron transport chain reactions initiated by photo‐induced charge separation, resulting in reductive fixation of carbon dioxide. Recently, photo‐bioelectrochemical cells in which photosynthetic electrons are introduced into an electrochemical circuit have attracted attention for solar energy harvesting and basic research on photosynthesis . For photo‐bioelectrochemical cells, biocatalysts including photosynthetic reaction centers, thylakoid membranes, and photosynthetic microbial cells need to be electrically wired to an anode indirectly via electron mediators or directly .…”
Section: Figurementioning
confidence: 99%